(untitled) (Journal of the College of Basic Education, 2026)
The trade relationship between the United States and China poses a direct challenge to the global trade system and has far-reaching implications for international law. This research examines the dimensions of trade relations, their historical path, and their impact on the American and Chinese systems through global trade laws and their strategic economic, security, and social dimensions. The study covers American concerns about China as a rising power, supported by its economic success in trade competition and its dominance and control of Asian markets, as well as concerns about China’s infiltration of the Asian trade infrastructure and its competition with the United States’ role in the region.